Long-Term Stability and Biocompatibility of Pericardial Bioprosthetic Heart Valves - Williams, David F.; Bezuidenhout, Deon; de Villiers, Jandre; Human, Paul; Zilla, Peter (Frontiers in Cardiovascular Medicine, 2021)
The use of bioprostheses for heart valve therapy has gradually evolved over several decades and both surgical and transcatheter devices are now highly successful. The rapid expansion of the transcatheter concept has clearly placed a significant onus on the need for improved production methods, particularly the pre-treatment of bovine pericardium. Two of the difficulties associated with the biocompatibility of bioprosthetic valves are the possibilities of immune responses and calcification, which have led to either catastrophic failure or slow dystrophic changes. These have been addressed by evolutionary trends in cross-linking and decellularization techniques and, over the last two decades, the improvements have resulted in somewhat greater durability. However, as the need to consider the use of bioprosthetic valves in younger patients has become an important clinical and sociological issue, the requirement for even greater longevity and safety is now paramount. This is especially true with respect to potential therapies for young people who are afflicted by rheumatic heart disease, mostly in low – to – middle income countries, for whom no clinically acceptable and cost-effective treatments currently exist. To extend longevity to this new level, it has been necessary to evaluate the mechanisms of pericardium biocompatibility, with special emphasis on the interplay between cross-linking, decellularization and anti-immunogenicity processes. These mechanisms are reviewed in this paper. On the basis of a better understanding of these mechanisms, a few alternative treatment protocols have been developed in the last few years. The most promising protocol here is based on a carefully designed combination of phases of tissue-protective decellularization with a finely-titrated cross-linking sequence. Such refined protocols offer considerable potential in the progress towards superior longevity of pericardial heart valves and introduce a scientific dimension beyond the largely disappointing ‘anti-calcification’ treatments of past decades.